REFERENCE-FREE REDUCTION OF BALLISTOCARDIOGRAM ARTIFACT FROM EEG DATA USING EMD-PCA - JAVED, EHTASFIAM (2014)
Contemporaneous Electroencephalograph (EEG) and functional Magnetic Resonance Image (fMRI) acquisitions provide a better insight to brain dynamics. Irrespective of the fact that this modality fusion provides advantages, the artifacts pose a threat to acquire a high quality of data. One such problematic artifact is the Ballistocardiogram (BCG) artifact. The BCG artifact has a dynamic effect i.e. complex in spatial, nonstationary in temporal and nonspecific signal in spectral domain. Despite several ef forts to find an appropriate methodology for removing BCG artifact, significant inconsistency exists between EEG-fMRI studies. This dissertation presents a referen.eefree hybrid algorithm which combines features of Empirical Mode Decomposition (EMD) with Principal Component Analysis (PCA) to reduce the BCG artifact. The algorithm does not require the recordings of Electrocardiogram (ECG), Electrooculogram (EOG) or the signals from motion sensors to extract the BCG artifact.